Amoebic psoas and liver abscesses. Issue 806 (December 1992) - O'Leary, C.; Finch, R.
Abstract : A 28 year old woman with a history of a dysenteric illness and documented Campylobacter infection presented with amoebic psoas and liver abscesses. A review of the literature of the last 20 years did not yield any reports of an amoebic psoas abscess.